Use of a macromolecular crowding agent to dissect interactions and define functions in transcriptional activation by a DNA-tracking protein: bacteriophage T4 gene 45 protein and late transcription. - Sanders, G M (1994)
We have used a molecular crowding reagent to define functions in the transcriptional activation of bacteriophage T4 late genes. This activation normally requires the three T4 DNA polymerase accessory proteins encoded by T4 genes 44, 62, and 45 (the gp44/62 complex and gp45), an enhancer-like cis-acting site, an RNA polymerase-bound coactivator, and an unobstructed path along the DNA joining the promoter to the enhancer. We show that molecular crowding eliminates the requirement for the gp44/62 complex and for the enhancer, retains the requirement for gp45 and its coactivator, and generates activated promoter complexes with nearly unchanged DNase I footprints. These experiments identify gp45 as the direct activator of transcription, and the gp44/62 complex as the assembly factor for gp45. They suggest that the enhancer serves as the normal, but not invariably essential, entry site for the gp45 DNA-tracking protein.